Survey of bovine leukemia virus genotypes from Thai swamp buffaloes raised in central and eastern Thailand - Chaikhun-Marcou, Thuchadaporn; Saekhow, Prayuth (Agriculture and Natural Resources, 2024)
Importance of the work: Bovine leukemia virus (BLV) is a known etiologic agent of enzootic bovine leukosis in cattle and has also been observed in buffaloes. The genotyping of BLV based on the gp51-env gene has been conducted exclusively in cattle, but there are no studies in buffaloes. Objectives: To identify the genotypes of BLV among Thai buffaloes raised in central and eastern Thailand. Materials & Methods: Polymerase chain reaction (PCR) and BLV-specific primers were used to perform proviral DNA detection of BLV. Then, the genotype was detected from nucleotide sequences of the gp51-env gene based on phylogenetic analysis. Results: Nested PCR showed that the occurrence of the BLV provirus in the Thai-buffalo blood samples was 23.1% (42/182). A phylogenetic tree assay showed that the 24 partial nucleotide sequences of the Thai swamp-buffalo BLV gp51-env gene belonged to genotype1. Evolutionary trees obtained from reference-cattle BLV nucleotide sequences selected based on similarity to a representative of Thai swamp-buffalo BLV nucleotide sequences (OB BLV6) were used to internally validate genotype 1. The buffalo-circulating BLV and bovine-circulating BLV were shown to be part of a distinct clade. Main finding: The evolutionary phylogenetic tree showed that all the samples were genotype 1, but there were significant differences between buffalo-circulating BLV and bovine-circulating BLV. Hence, some features may diverge, at least in the gp51-env genes.